The Role of the European Union in Palestinian State-Building - Seidner, Marton (European Scientific Journal, ESJ, 2023)
This paper examines the role of the European Union (EU) in creating a Palestinian state and whether there is a coherent unity among EU Member States regarding its recognition. The research hypothesis is that EU Member States do not unanimously recognize the legitimacy of a Palestinian state, despite the EU’s collective belief in creating a two-state solution. The methodology combines qualitative and quantitative research. The qualitative research involves understanding political processes and analyzing relevant scientific studies and documents. The quantitative research involves statistical analysis of voting outcomes of EU Member States in the UN General Assembly (UNGA). The analysis of UNGA resolutions between 2012 and 2022 found that there is no coherent unity among EU Member States regarding the recognition of a Palestinian state. Although the EU collectively supports a two-state solution, the foreign policy used has been insufficient to overcome the deep-rooted conflicts. In conclusion, the research suggests that a more effective approach is required to overcome the deep-rooted conflicts and achieve a common ground concerning the recognition of a Palestinian state. There is a need for a shift in the political and legal framework, which may be influenced by potential geopolitical reorganization in the Middle East.